Effect of ABT-4 on Seedling Growth Chlorophyll are Some Free Aminoacid Content in Buckwheat (Fagopyrum Esculentum Moench) - Prasad, B. N.; Paudel, R. (Tribhuvan University Journal, 2010)
Available with Full text. Key words: Seedling growth; Aminoacid; Buckwheat Tribhuvan University Journal Vol. XIX, 1996 Page: 25-31 Uploaded Date: 22 Nov., 2010